Diet and endoparasites of the lizard Gymnodactylus darwinii (Gekkota, Phyllodactylidae) from an Atlantic Rainforest area in southeastern Brazil - Mauricio Almeida-Gomes; Davor Vrcibradic; Thiago Maia-Carneiro; Carlos Frederico Duarte Rocha (Biotemas)
In this study we provide information on diet and endoparasites of individuals of the species Gymnodactylus darwinii in an Atlantic Rainforest area in the state of Rio de Janeiro, Brazil. Regarding diet, orthopterans and isopods were the most important preys. One nematode species (Physaloptera sp.) was found associated to the stomach of an individual, representing a new host record for this genus. Our results indicate that G. darwinii has a similar diet to other lizard species from the Atlantic Rainforest, although different from that of other congeneric species inhabiting open areas.